Diagnostic Value of Serum Biomarkers for Differentiating Central and Peripheral Causes of Acute Vertigo - Sohn, Jong-Hee; Kim, Chul-Ho; Lee, Sang-Hwa; Kim, Jong Ho; Lee, Jae Jun (Frontiers in Medicine, 2020)
Background: In patients presenting with acute vertigo or dizziness, distinguishing central from peripheral is a diagnostic challenge. This study investigated potential serum markers for differentiating central and peripheral vertigo in patients with acute-onset vertigo. Methods: This prospective case–control study recruited consecutive participants from the Emergency Department, including patients with acute-onset vertigo or dizziness within 12 h and control subjects. We used enzyme-linked immunosorbent assays to measure the serum S100β, NSE, BDNF, GFAP, and IL-6 levels during the acute period. Results: The 114 study subjects included 28 patients with central vertigo (CV), 49 patients with peripheral vertigo (PV), and 37 age- and sex-matched healthy controls. No differences were found in risk factor distribution among the three groups. In patients with CV, the serum NSE and S100β levels were significantly (p < 0.05) elevated compared with the control and PV groups. The ROC analysis gave an AUC of 0.843 (95% CI = 0.753–0.932) for NSE and 0.787 (95% CI = 0.687–0.886) for S100β for predicting CV. However, there were no significant differences in the serum GFAP and BDNF levels among the CV, PV, and control groups. Conclusions: Serum NSE and S100β levels are significantly higher in patients with CV, such as occurs with posterior circulation ischemic stroke or vertebrobasilar insufficiency. S100β and NSE may serve as serum biomarkers for differentiating between CV and PV in patients with acute-onset vertigo.